Relations between the Orthodox and the Anglicans in the Twentieth Century: A Reason to Consider the Present and the Future of the Theological Dialogue - Stathokosta, Vassiliki El. (Ecclesiology, 2012)
Taking as a starting point the Patriarchal Encyclical of 1902-4, which celebrates one hundred and ten years in 2012 (1902-2012), attention is given to its contribution to Anglican-Orthodox dialogue. A decisive landmark in Anglican-Orthodox relations and in the formation of the Ecumenical Movement was the visit of the Greek Church delegation to the USA and England in 1918 and the discussions with Episcopalians and Anglicans on Christology and Triadology (‘Trinitarian theology’) as well as ecclesiology. The process of this dialogue is examined here through the evaluations of three distinguished Greek Orthodox figures, carefully chosen as representative of their time, and in the light of such innovations as the ordination of women. This study emphasizes that the ecclesiological and theological proximity of Orthodoxy and Anglicanism is a solid basis for the continuation of their theological dialogue. The documents of Moscow (1976), Dublin (1984) and the Cyprus Statement (2006) prove that there is sufficient common ground to continue a fruitful discussion.